STUDY KEBERADAAN EKTOPARASIT Octolasmis sp. PADA KEPITING BAKAU (Scylla serrata) JANTAN DAN BETINA PADA PERTAMBAKAN SEMARANG - Wardhani, Catleya Kusuma; Sarjito, - -; Haditomo, Alfabetian Harjuno Condro (Journal of Aquaculture Management and Technology, 2018)
Kepiting bakau (Scylla serrata) merupakan salah satu komoditas andalan perikanan yang bernilai ekonomis tinggi, namun kendala yang sering dihadapi dalam proses perkembangan budidaya adalah infeksi parasit yang dapat menurunkan produksi budidaya yaitu parasit Octolasmis sp. Tujuan penelitian ini adalah mengetahui jenis-jenis parasit Octolasmis sp. yang menginfeksi kepiting bakau di pertambakan Semarang dan mengetahui tingkat infestasi parasit Octolasmis sp. pada kepiting jantan dan betina. Peneltian ini menggunakan metode eksploratif dan teknik metode random sampling. Kepiting yang diidentifikasi sebanyak 100 ekor dengan perbandingan jantan dan betina 1 : 1 yang diperoleh dari 4 sumber tambak dengan masing-masing berjumlah 25 ekor kepiting, dengan ukuran panjang karapaks7-11 cm dengan nilai rerata panjang karapaks 8,6 ± 0,73cm dan beratbobot 54-188 g dengan nila irerata112,68 ± 23,29 g. Hasil penelitian menunjukan bahwa jenis Octolasmis sp. yang teridentifikasi menyerang kepiting bakau pada pertambakan Semarang yaitu Octolasmis cor dan Octolasmis angulata. Tingkat infeksi parasit Octolasmis berdasarkan jumlah parasit yang ditemukan, pada kepiting betina parasit Octolasmis menginfeksi sebesar 68,09% dengan jumlah parasit O. cor sebesar 36,7% dan jumlah O. angulata sebesar 31,37%, sedangkan pada kepiting jantan parasit Octolasmis menginfeksi sebesar 31,9% dengan jumlah parasit O. cor sebesar 18,42% dan jumlah O. angulata sebesar 13,49%. Tingkat infeksi parasit Octolasmis berdasarkan jumlah parasit yang ditemukan lebih banyak menginfeksi kepiting betina daripada kepiting jantan.Mud crab (Scyllaserrata) is aaquaculture commodity that has a high economic value, however the constraints that are often found in aquaculture process is parasite infection, that can reduce the production of aquaculture is called parasite Octolasmissp.. The purpose of this study was to determine the types of parasites Octolasmissp. who infects mud crabs in Semarang ponds and to determine the level of Octolasmissp. parasite infestation between male and female crabs.This research uses explorative method and random sampling method technique. The crab identified as many as 100 crabs with a ratio of male and female 1:1 obtained from 4 sources of pounds with 25 crabs each, with leght of carapace is 7-11 cm with the average length is 8.6 ± 0.73 cm and the weight is 54-188 g with the mean of weight is 112.68 ± 23.29 g.The results showed that the type of Octolasmissp. who were identified to attack mud crabs at Semarang pounds is Octolasmiscor and Octolasmis angulata. Octolasmis parasite infection rate based on the number of parasites found, on female crab Octolasmis parasite infected 68.09% with the number of parasites O. cor is 36.7% and the number of O. angulata is 31.37%, meanwhile on male crab Octolasmis parasite infected 31.9% with the number of parasites O. cor is 18.42% and the number of O. angulata is 13.49%. The rate of parasitic infection of Octolasmis based on the number of parasites found more infects female crabs than male crabs.Mud crab (Scyllaserrata) is aaquaculture commodity that has a high economic value, however the constraints that are often found in aquaculture process is parasite infection, that can reduce the production of aquaculture is called parasite Octolasmissp.. The purpose of this study was to determine the types of parasites Octolasmissp. who infects mud crabs in Semarang ponds and to determine the level of Octolasmissp. parasite infestation between male and female crabs.This research uses explorative method and random sampling method technique. The crab identified as many as 100 crabs with a ratio of male and female 1:1 obtained from 4 sources of pounds with 25 crabs each, with leght of carapace is 7-11 cm with the average length is 8.6 ± 0.73 cm and the weight is 54-188 g with the mean of weight is 112.68 ± 23.29 g.The results showed that the type of Octolasmissp. who were identified to attack mud crabs at Semarang pounds is Octolasmiscor and Octolasmis angulata. Octolasmis parasite infection rate based on the number of parasites found, on female crab Octolasmis parasite infected 68.09% with the number of parasites O. cor is 36.7% and the number of O. angulata is 31.37%, meanwhile on male crab Octolasmis parasite infected 31.9% with the number of parasites O. cor is 18.42% and the number of O. angulata is 13.49%. The rate of parasitic infection of Octolasmis based on the number of parasites found more infects female crabs than male crabs.